The Effect of CAR, FDR, BOP, and ROA on NPF at Islamic Commercial Banks in Indonesia for the 2019-2023 Period - Aini, Lathifah; Sinaga, Era Widia; Fayza, Salsabila; Rambe, Rolil; Rozaini, Noni; Nasution, Armin Rahmansyah (Jurnal Iqtisaduna, 2025)
This study aims to explore the relationship between key financial ratios-Capital Adequacy Ratio (CAR), Financing to Deposit Ratio (FDR), Operating Expenses per Operating Income (BOPO), and Return on Assets (ROA)-to the phenomenon of non-performing financing in Indonesian Islamic banking institutions during the period 2019-2023. Using a quantitative approach and multiple regression analysis method, this study utilizes data from the financial supervisory authority. The results of the analysis show that separately, only FDR and BOPO have a significant impact on Non-Performing Financing (NPF), while CAR and ROA show no significant effect. However, the results of simultaneous testing show that the four independent variables together have a considerable influence on the level of non-performing financing, with the level of determination reaching 71.72%. This finding emphasizes the importance for Islamic banks to improve efficiency in operational practices and implement more targeted financing distribution policies, as a strategic step to reduce the number of non-performing loans and strengthen financial stability in the Islamic banking ecosystem in Indonesia.